A Bioversity–CIAT partnership helped integrate gender considerations into ISEAL’s code of good practices for sustainability systems - Elias, Marlene; Morgan, Miranda Yeen (2025)
A 3-year partnership with the Alliance of Bioversity International and CIAT helped better assess and promote gender equality in agrifood-related sustainability systems. Gender researchers from the Alliance of Bioversity & CIAT and the ISEAL Alliance produced demand-driven resources and learning events to support this gender work. The collaboration strengthened capacities and knowledge among ISEAL members and led to the integration gender considerations in the latest revision of the ISEAL Code of Good Practices for Sustainability Systems.